2019
DOI: 10.3390/geriatrics4030048
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Digital Dysphagia Guide with Care Homes: Co-Production and Evaluation of a Nutrition Support Tool

Abstract: Good nutrition is a recognised outcome in the health and well-being of older care home residents and dysphagia is a known risk factor associated with under nutrition and poor outcomes. The study co-produced a digital Dysphagia Guide with Care Homes using a consensus method with interviews and focus groups to prioritise the need for information and explore acceptability of an educational tool for care home workers. Evaluation of use, acceptability of design, and content of the guide were completed via remote mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…All studies were completed in high income countries and the lead author of most studies (n = 12) were based in the UK. 12 studies used qualitative research methods [17,18,[27][28][29][30][31][32][33][34][35][36], six used mixed methods [37][38][39][40][41][42] and one was a descriptive piece about a collaborative partnership approach [43]. 15 studies reported using participatory research methodologies, with nine using participatory action research approaches [17,18,28,29,31,35,37,38,41] and four using appreciative inquiry [27,30,33,39].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were completed in high income countries and the lead author of most studies (n = 12) were based in the UK. 12 studies used qualitative research methods [17,18,[27][28][29][30][31][32][33][34][35][36], six used mixed methods [37][38][39][40][41][42] and one was a descriptive piece about a collaborative partnership approach [43]. 15 studies reported using participatory research methodologies, with nine using participatory action research approaches [17,18,28,29,31,35,37,38,41] and four using appreciative inquiry [27,30,33,39].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…15 studies reported using participatory research methodologies, with nine using participatory action research approaches [17,18,28,29,31,35,37,38,41] and four using appreciative inquiry [27,30,33,39]. Collaborative enquiry [36], experienced-based co-design [42] and nominal group methods [42] were used once respectively.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations